2019
DOI: 10.1038/s41598-019-46732-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on intracellular delivery of liposome encapsulated quantum dots using advanced fluorescence microscopy

Abstract: Quantum dots increasingly gain popularity for in vivo applications. However, their delivery and accumulation into cells can be challenging and there is still lack of detailed information. Thereby, the application of advanced fluorescence techniques can expand the portfolio of useful parameters for a more comprehensive evaluation. Here, we encapsulated hydrophilic quantum dots into liposomes for studying cellular uptake of these so-called lipodots into living cells. First, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 88 publications
(106 reference statements)
2
14
0
Order By: Relevance
“…Therefore, the prepared QD-liposomes are within the recommended size as suitable nanocarriers delivering QDs to the cancer cells. While previous studies have reported no significant change in the hydrodynamic size of the liposomes following encapsulation [19,[28][29][30], other studies have reported an increase in the size of these nanovehicles when they encapsulate QDs [31,32]. The differences in the reported findings could be due to different liposomal formulations and preparation techniques used among studies.…”
Section: Characterization Of the Prepared Qd-loaded Liposomesmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, the prepared QD-liposomes are within the recommended size as suitable nanocarriers delivering QDs to the cancer cells. While previous studies have reported no significant change in the hydrodynamic size of the liposomes following encapsulation [19,[28][29][30], other studies have reported an increase in the size of these nanovehicles when they encapsulate QDs [31,32]. The differences in the reported findings could be due to different liposomal formulations and preparation techniques used among studies.…”
Section: Characterization Of the Prepared Qd-loaded Liposomesmentioning
confidence: 80%
“…Several studies have shown a successful encapsulation of QDs either inside the bilayer membrane or in the core of the liposomes encapsulating therapeutic agents. These studies showed safer drug delivery and optical tracking, thus providing opportunities to create an effective theranostic nanoscale delivery system, where both diagnostic and therapeutic functions can be given in a single dose [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various optical imaging techniques that allow for the observation of lipid-based nanostructures, confocal laser scanning microscopy (CLSM) is a method of choice, since it facilitates the structural investigation (in an almost non-invasive way) by visualizing the liposomes’ internal structures [ 170 ]. It also allows for localizing (and quantifying) the extent of liposomes’ subcellular distribution during the drug-delivery processes [ 176 , 177 , 178 , 179 ]. CLSM is a crucial technique for the characterization of biomaterials and biological specimens with high-resolution images.…”
Section: Characterization Methods Of Liposome Nanocarriersmentioning
confidence: 99%
“…Soft nanocompartments (liposomes and polymersomes) are an appealing alternative for development of nanotheranostics because their architecture, consisting of an aqueous cavity surrounded by a layer with hydrophobic core, allows simultaneous loading of hydrophilic and hydrophobic molecules/nanostructures (small molecules, proteins, inorganic nanoparticles, DNAs, etc). [15][16][17][18][19][20] In particular, polymersomes based on amphiphilic block copolymers have advantages over lipidic compartments, such as increased mechanical stability and greater chemical versatility, which is useful to control membrane properties, such as stimuli-responsiveness, and programmability. [21,22] Polymersomes have been used both for co-delivery of drugs and imaging agents [23,24] and for development of catalytic compartments that mediate specific reactions inside the lumen.…”
Section: Introductionmentioning
confidence: 99%